Consumers' preferences and willingness to pay for improved environmental standards: insights from cane sugar in the Great Barrier Reef region. (20th June 2022) - De Valck, Jeremy; Rolfe, John; Rajapaksa, Darshana; Star, Megan
Abstract : Reducing nutrient runoff from sugarcane production into the Great Barrier Reef (GBR) has become a major policy focus for the Queensland and Australian Governments. This study explores consumer willingness to pay (WTP) to achieve higher environmental standards for sugar originating from the GBR catchments, through the use of a GBR‐safe ecolabel. A Best‐Worst Scaling (BWS) and a Contingent Valuation (CV) experiment are conducted on a random sample of 1, 100 Australian residents. The BWS experiment reveals that personal health considerations are more important than sustainability and environmental factors, including impacts on the GBR. Results of the CV experiment show that respondents are more likely to pay a premium to support Reef‐friendly sugar if they are living in urban areas, plan to visit the GBR in the future, think that the GBR condition has declined, and are generally concerned about keeping a healthy diet. We estimate that the average WTP is $24.5/year/household, which only represents 0.34 per cent of the average weekly grocery bill of Australian households. This small contribution through increased sugar prices could conservatively raise $46.9M/year in support of sugar producers to improve water quality in the GBR. Based on these results, we recommend policy‐makers consider instruments that further involve sugar consumers.